Comparitive studies on certain Bio-Chemical constituents of Anoestrus Cross Bred Jersey Rural Cows - RAMKRISHNA, K V (The Indian Journal of Animal Reproduction, 2023)
Serum samples of 35 anoestrus cross bred jersey cows of 4-61/2 years age group were processed for some biochemical constituents and . were compared with equal number . of cycling . animals of same age group. Significantly low • levels of haemoglobin, cholesterol, glucos~. . inorganic phosphon,is, and serum iron were J recorded.
Keywords: Bio-Chemical constituents; Anoestrus; Jersy rural cow